Linguacultural features of toponymic units in the example of Bukhara region - Kobilova , Aziza; Rakhmatova , Aziza (The Lingua Spectrum, 2025)
This study investigates the linguacultural characteristics of the toponymic system specifically in the example of Bukhara region, emphasizing their historical, semantic, and cultural significance. As a historic Silk Road center, Bukhara has absorbed influences from Persian, Arabic, Turkic, and Russian languages, all of which are reflected in its geographical names. The research categorizes Bukhara’s toponyms into religious, geographical, economic, and ethnic groups, analyzing their historical context and linguistic evolution. The findings suggest that Bukhara’s toponyms function as a cultural and historical archive, preserving the city’s legacy and demonstrating linguistic interconnections across civilizations.